2019
DOI: 10.1080/15213269.2019.1572522
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making about broad- and narrowcasting: a neuroscientific perspective

Abstract: What differentiates sharing with few, well-defined others (narrowcasting) from sharing with loosely defined crowds (broadcasting)? One possibility involves a trade-off where broadcasting is selffocused and self-serving, and narrowcasting is based on otheroriented, altruistic motives. We present neuroimaging data consistent with a second, parallel-processes perspective. According to this account, both narrow-and broadcasting simultaneously involve self-related and social motives since these concepts are strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 65 publications
(119 reference statements)
4
17
0
Order By: Relevance
“…Context effects have also been found in the study of sharing decisions. For instance, the size of a sharer's potential audience impacts the extent to which brain regions, known to be important in sharing decisions, are engaged during decisions about news sharing [7]. Further, while making sharing decisions about news articles, participants wo identified as avid news readers showed greater functional connectivity between the neural valuation system and brain areas often associated with deliberate/effortful processing [57].…”
Section: Context-dependent Valuation Of Media and Social Influencementioning
confidence: 99%
See 1 more Smart Citation
“…Context effects have also been found in the study of sharing decisions. For instance, the size of a sharer's potential audience impacts the extent to which brain regions, known to be important in sharing decisions, are engaged during decisions about news sharing [7]. Further, while making sharing decisions about news articles, participants wo identified as avid news readers showed greater functional connectivity between the neural valuation system and brain areas often associated with deliberate/effortful processing [57].…”
Section: Context-dependent Valuation Of Media and Social Influencementioning
confidence: 99%
“…As this example illustrates, when deciding whether to share media content with others, potential sharers usually integrate at least two types of information, namely information about the media content itself [4,5] (e.g. its credibility, relevance, or usefulness) and about relevant social influences, including perceived social norms or opinions expressed by peers, for instance those the content could be shared with [6,7]. For Anna, integrating two such inherently incomparable inputs to decide what information to share is akin to comparing proverbial apples and oranges.…”
Section: Introductionmentioning
confidence: 99%
“…More broadly, as briefly mentioned before, an important information characteristic is whether it originates from mass media or interpersonal sources (corresponding to differ ent steps in the propagation chain shown in Figure 16.1). Communication scientists have demonstrated that information sources can differ in trustworthiness and persuasiveness (Hesse et al, 2005;Katz & Lazarsfeld, 1955), among other characteristics, (p. 299) and work on the diffusion of innovations suggests that the relative importance of mass media and interpersonal sources may vary over time (Rogers, 2010). Indeed, there is a compli cated interplay between mass media broadcasts and interpersonal communication, involv ing both mediating and moderating relationships (Southwell & Yzer, 2007;van den Putte, Yzer, Southwell, de Bruijn, & Willemsen, 2011).…”
Section: Communication Channel Characteristicsmentioning
confidence: 99%
“…Finally, cultural characteristics are known to affect social interactions as well as the flow of information in numerous ways (e.g., Rogers, 2010;Triandis, 2001), yet the neural mechanisms of sharing have almost exclusively been studied in American college stu dents. To provide an example of a possible hypothesis, in cultures with more independent self-construals that emphasize the individual over the group (Hofstede, Hofstede, & Minkov, 1991), sharers might rely less on perceived social outcomes when estimating in formation-sharing value than do sharers in collectivistic cultures, which emphasize groups over individuals.…”
Section: Culturementioning
confidence: 99%
“…2010 ) and that making sharing decisions intensifies the activations of these brain areas ( Baek et al. 2017 ; Scholz et al. 2020 ).…”
Section: Introductionmentioning
confidence: 99%